2007
DOI: 10.1534/genetics.107.071720
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the 1.688 Satellite DNA Family Is Under the Control of RNA Interference Machinery inDrosophila melanogasterOvaries

Abstract: Here we show that RNA interference (RNAi) machinery operates in Drosophila melanogaster 1.688 satellite transcription. Mutation in the spn-E gene, known to be involved in RNAi in the oocytes, causes an increase of satellite transcript abundance. Transcripts of both strands of 1.688 satellite repeats in germinal tissues were detected. The strength of the effects of the spn-E mutation differs for 1.688 satellite DNA subfamilies and is more pronounced for autosomal pericentromeric satellites compared to the X-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 40 publications
5
63
0
Order By: Relevance
“…Recent studies support the contention that the transcription of this satDNA in ovaries could be under the control of RNAi machinery to maintain the silenced state of these centromeric and pericentromeric repeats (Usakin et al, 2007).…”
Section: Introductionmentioning
confidence: 75%
“…Recent studies support the contention that the transcription of this satDNA in ovaries could be under the control of RNAi machinery to maintain the silenced state of these centromeric and pericentromeric repeats (Usakin et al, 2007).…”
Section: Introductionmentioning
confidence: 75%
“…It has been established that particular RNAs expressed in the maternal germline are processed into a special class of small RNAs called piRNAs that act to silence gene expression. RNAs homologous to the 359-bp repeat were found in the germinal tissues, and the abundance of these transcripts was increased in mutants defective in components in the piRNA pathway, suggesting that transcription of these sequences occurs and that the piRNA pathway targets this expression (Usakin et al 2007). Current understanding of piRNA suppression of the expression of repeated sequences suggests that copies of the sequence in a specialized piRNA cluster in heterochromatic regions are expressed, processed, and loaded onto an Argonaut protein called Piwi.…”
Section: Controlling Heterochromatinization In Time and Space At The Mbtmentioning
confidence: 99%
“…Consequently, 1.688 arrays contribute to provide individual structural identities to chromosomes (see Kuhn et al, 2012;Gallach, 2014; and references therein). Usakin et al (2007) were the first to show that the repeats from the 1.688 satDNA family are transcribed in embryos and adult flies. They found that 1.688 double-stranded RNAs derived from subfamilies located on chromosomes 2 and 3 are processed into siRNAs (small interfering RNAs) that in turn participate in the heterochromatin formation of both chromosomes.…”
mentioning
confidence: 99%